2006
DOI: 10.4314/bcse.v20i1.21142
|View full text |Cite
|
Sign up to set email alerts
|

<b>PREPARATION, SPECTROSCOPIC STUDIES AND X-RAY STRUCTURE OF HOMOBINUCLEAR LANTHANIDE(III) COMPLEXES DERIVED FROM 2,6-DIFORMYL-4-CHLOROPHÉNOL-BIS-(2'-HYDROXY-BENZOYLHYDRAZONE)</b>

Abstract: ABSTRACT. Reaction of the 2,6-diformyl-4-chlorophenol-bis-(2'-hydroxy-benzoylhydrazone) with Ln(NO3)3.nH2O (n = 5 or 6 and Ln = Y, La, Ce, Pr, Nd, Sm, Gd, Dy, Er and Yb) produces homobinuclear complexes. These complexes have been characterized by analysis, molar conductance, magnetic measurements, infrared spectral studies and X-ray diffraction. The analytical data showed 1:3 (metal:ligand) stoichiometry. Molar conductance measurements in dmf indicate 1:3 electrolytes in all cases. Magnetic moment values are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…These complexes are particularly interesting in various fields such as magnetism [6], catalysis [7], in medicine [8], and luminescence [9,10]. The presence of phenolic moiety suggests that these complexes can be antioxidants as reported in the literature [11] but also as antibacterial agents [12,13]. In recent studies, nicotinic hydrazide complexes were prepared and showed enzyme-like activities [14,15].…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…These complexes are particularly interesting in various fields such as magnetism [6], catalysis [7], in medicine [8], and luminescence [9,10]. The presence of phenolic moiety suggests that these complexes can be antioxidants as reported in the literature [11] but also as antibacterial agents [12,13]. In recent studies, nicotinic hydrazide complexes were prepared and showed enzyme-like activities [14,15].…”
Section: Introductionmentioning
confidence: 91%
“…In addition to these signals, two singlets are identified at 8.73 and 9.01 ppm and each integrating a proton attributed respectively to the proton H15 and that of NH [21]. The 13 C NMR spectrum indicates the signal of the carbon of the carbonyl function (C=O) at 160.10 ppm and that of the carbon of the imine function (C=N) at 148.91 ppm [9,11]. The signal in the range 123.10-148.34 are assigned to the aromatic carbon atoms.…”
Section: General Studymentioning
confidence: 99%
See 1 more Smart Citation